Effect of sugar beet pectin on oil uptake in fried banana and its acceptability / Siti Suhara Ramli and Aini `Izzati Mohd Rosdi - Ramli, Siti Suhara; Mohd Rosdi, Aini `Izzati (Universiti Teknologi MARA Cawangan Pulau Pinang, 2019)
Fried banana is one of the popular local snacks in Malaysia. However, tremendous interest in healthy food has risen among consumers and producers resulting in a rising demand for low-fat foods. Thus, oil uptake needs to be considered during frying since it also affects the flavour, odour and general organoleptic properties of the food. The main objective of this study is to determine the effect of different concentrations of sugar beet pectin in the frying batter of fried banana and introduce the new usage of sugar beet pectin as one of the ingredients in the frying batter. Three different formulations of frying batter were prepared using 1%, 1.5% and 2% of sugar beet pectin (SBP) together with other ingredients including rice flour, water, plain flour, baking powder and salt. The addition of sugar beet pectin improved the characteristic of the batter as well as the fried banana crust. The moisture content of the crust increased about 7.6% when 1.5% SBP (F2) was used in the formulation thereby reducing the oil absorption by 8.5%. The crust crispiness also increased by 16.7% when 1.5% SBP (F2) was added to the frying batter formulation. Batter pick-up value was found highest in F1 (1% SBP) with 8.84% increment as compared to batter with no added hydrocolloids. Addition of SBP in batter formulations significantly increased the batter pick-up value. In terms of acceptability, F1 (1% SBP) was the most preferred by the panellist which was due to the appearance and colour of the fried bananas. All formulations obtained attributes scores higher than six thus were accepted by the panellists.